1999
DOI: 10.1097/00000658-199904000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Zero-Balanced Hemofiltration on the Course of Severe Experimental Pancreatitis in Pigs

Abstract: ObjectiveTo examine the impact of continuous venovenous hemofiltration (CVVH) on the course of experimental pancreatitis in pigs. Summary Background DataThe activation of different mediator cascades is assumed to trigger multiple organ dysfunction or failure during necrotizing pancreatitis. CVVH has been suggested to be beneficial in those instances by eliminating several inflammatory mediators released in the circulation. MethodsPancreatitis was induced by a combined intraductal injection of sodium taurochola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 27 publications
1
20
0
1
Order By: Relevance
“…This results in an imbalance between pro-and anti-inflammatory cytokines, resulting in the development of SIRS. Some mediators, such as TNF-alpha, phospholipase, and kinin, are increased greatly in animal models of SAP [9] , and some studies have shown that there is a significant correlation between the serum levels of IL-1-beta, IL-6, IL-8, IL-10 and IL-11 and the severity of acute pancreatitis [24][25][26][27] . Animal studies have shown that early blockade of the cytokine cascade at the level of the IL-1 receptor significantly decreases the severity of pancreatitis and intrinsic pancreatic damage, as well as the mortality from SAP [28,29] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This results in an imbalance between pro-and anti-inflammatory cytokines, resulting in the development of SIRS. Some mediators, such as TNF-alpha, phospholipase, and kinin, are increased greatly in animal models of SAP [9] , and some studies have shown that there is a significant correlation between the serum levels of IL-1-beta, IL-6, IL-8, IL-10 and IL-11 and the severity of acute pancreatitis [24][25][26][27] . Animal studies have shown that early blockade of the cytokine cascade at the level of the IL-1 receptor significantly decreases the severity of pancreatitis and intrinsic pancreatic damage, as well as the mortality from SAP [28,29] .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, VVH www.wjgnet.com may directly inhibit the cells that contribute to the systematic response [8] . The use of continuous veno-venous hemofiltration (CVVH) has been assessed in a animal model of SAP and was found to significantly improve the survival time, when used both for therapeutic and prophylactic treatment, especially the latter [9] . However, the efficiency of treatment decreased with continuing use of CVVH, suggesting that the filter membranes were compromised by long-term application [9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this a model of experimental pancreatitis [8] mediating SIRS or even septic disease associated with hemodynamic insufficiencies was used. However, classical criteria of systemic inflammatory disease in humans such as body temperature higher than 39.0°C, tachycardia, tachypnea, and leukocystia or leukopenia are in the physiological range in animals [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…1 body weight during a 1 minute period was performed as described also were. 10,11 MB infusion. MB (Merck Diagnostica, Darmstadt, Germany) infusion was carried through an initial dose of 2mg.kg-1 body weight diluted in 20 ml of 0,9% sodium chloride solution followed by a maintenance dose of 2 mg.kg-1 body weight.h-1 was done by a continuous intravenous infusion throughout the experiment.…”
mentioning
confidence: 99%